Exploring sustainability case studies on Filipino film distribution via online streaming platforms after COVID-19 pandemic - See, Christine Joy P.; Palileo, Shirley (Quezon City University of the Philippines, Diliman, 2025)
This study examines the sustainability of Filipino film distribution via online streaming platforms in the post-COVID-19 era. The COVID-19 pandemic accelerated a shift to online streaming, offering new ways to reach audiences despite cinema closures. The research addresses three main questions: (1) What are the advantages and disadvantages of the shift to online film distribution during and after the pandemic? (2) How do changes in distribution methods influence the film industry? and (3) What model can be developed that anticipates the future of film distribution in the new normal and beyond? This research explores how online streaming has reshaped film distribution by integrating Raymond Williams’ Emergent Culture Theory, Clayton Christensen’s Disruptive Innovation Theory, and David Throsby’s Culturally Sustainable Development Theory.
Qualitative interviews with industry experts reveal the opportunities and challenges of the digital shift, including enhanced accessibility, digital infrastructure, and market competition. Findings suggest a transformative film distribution model, such as combining theatrical releases with online streaming, for a sustainable approach that adapts to changing industry dynamics and consumer habits, preserving the relevance of Filipino cinema. This research lays a foundation for future exploration of business model in film distribution and broader creative sectors to sustain film’s cultural and economic vitality.
Thesis
Keywords: Motion pictures -- Distribution -- Philippines; Motion pictures -- Production and direction -- Philippines; COVID-19 Pandemic, 2020-2023 -- Philippines -- Economic aspects